EMERGING POLLUTANTS: OCCURRENCE, FATE, TOXICOLOGICAL IMPACTS AND REMOVAL TECHNOLOGIES - Sonam; Kushwaha R.; Tripathi P.; Singh R.S.; Mohan D. (My University, 2025)
The presence of emerging contaminants in the effluents of wastewater treatment plants is a matter of growing concern. Emerging contaminants are chemical compounds including pesticides, pharmaceuticals, hormones, other endocrine disruptors, surfactants, surfactant metabolites, industrial additives and personal care products. The occurrence of various emerging pollutants is often related to discharges from treatment plants, as a consequence of the extensive use of such compounds and the lack of efficient removal technologies. The list of compounds considered as emerging pollutants has increased significantly in recent years leading to a number of parent compounds and transformation products found in wastewater effluent, surface and groundwater and drinking water. The identification and quantification of these compounds in water or wastewater has become a major scientific task requiring highly sophisticated analytical methodologies which can detect even minute levels of pollutants. The quantification of emerging contaminants in complex waste water samples recognized through non-target screening approaches, has played a key role in the planning and design of water treatment facilities. A majority of emerging contaminants do not have standard regulations and could lead to lethal effects on human and aquatic life even at small concentrations. The conventional primary and secondary water treatment plants do not remove or degrade these toxic pollutants efficiently and hence need cost effective tertiary treatment method. Currently, membrane filtration technologies and the use of advanced oxidation processes (AOPs) are widely studied for the removal of micropollutants, either in wastewater or in drinking water. Among these treatments, the most relevant processes include ozonation, photocatalysis, electrochemical reactions, membrane bioreactors, nanofiltration or ultrafiltration, reverse osmosis and adsorption. Adsorption is a promising method for removal of pollutants, because of low initial cost for implementation, highly-efficient and has simple operating design. Research has shown that the application of different adsorbents such as activated carbons, modified bio-chars, nano-adsorbents (carbon nanotubes and graphene), composite adsorbents, and others are being used for removal of emerging contaminants from water and wastewater. Technologies based on hydrogen peroxide oxidation, such as Fenton or others activated by UV and ultrasound have also proved significant. The various sources and types of emerging pollutants along with their toxicological effect on health and environment have been highlighted. The review further focusses on the information about advancements in wastewater treatment technologies such as constructed wetland (CW) and advanced oxidation processes (AOPs) and the fate of emerging contaminants during these treatments. The ecological effects of these contaminants and their by-products formed during advanced treatment processes as well as different analytical techniques for the analysis of emerging contaminants have also been discussed. © 2021 by Nova Science Publishers, Inc.